Effective Learning Management to Improve Student Learning Achievement in Madrasah - Azwar Annas; Ehwanudin Ehwanudin; Eka Fitria Ningsih (Assyfa Journal of Islamic Studies, 2024)
Student learning achievement in Indonesian madrasahs still faces significant challenges, as reflected in the results of the Indonesian Madrasah Competency Assessment (AKMI), which indicates the need for improved learning quality across various educational levels. Effective learning management becomes a key factor in optimizing student learning achievement; however, its implementation in madrasahs still encounters various obstacles such as limited resources, varying teacher competencies, and lack of technology integration in learning. This study aims to analyze the implementation of effective learning management and its impact on improving student learning achievement in madrasahs, focusing on planning, implementation, and evaluation of learning. Using a qualitative case study approach, data were collected through in-depth interviews with madrasah principals, teachers, and students, observation of learning processes, and documentation of learning outcomes in a madrasah in Lampung Province. The findings indicate that effective learning management is implemented through three main stages: learning planning involving student needs analysis and development of contextual learning tools; learning implementation integrating active, innovative, and technology-based methods; and comprehensive and continuous learning evaluation. The integration of student-centered learning approaches, utilization of digital technology, and strengthening of madrasah literacy culture have contributed to significant improvements in student learning achievement. Supporting factors include visionary principal leadership, professional teacher competence, and infrastructure support, while inhibiting factors include budget limitations, low digital literacy, and lack of parental involvement. This study concludes that effective learning management offers a systemic approach to improving student learning achievement in madrasahs through strengthening planning, implementation, and evaluation of learning oriented toward student needs and potential.